Service Learning Model In Community Service: Effectiveness Analysis Of KKNT Program On Religious Literacy Enhancement In Tanjung Dalam Village - Afandi, Ahmad; Jafar Sidiq; Manulu, Frian Rifqi; Muhammad Rafi Zulkarnaen; Muhammad Fauzan Al-Akbar (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
The Thematic Community Service Program (Kuliah Kerja Nyata Tematik/KKNT), based on Service Learning in rural areas, faces challenges in creating transformative and sustainable impacts on community religious literacy. This community service aims to analyze the effectiveness of the Service Learning model in improving the religious literacy of students and communities through KKNT programs in Tanjung Dalam Village, Ulok Kupai District, Bengkulu, during Ramadhan 2025. The study employed a participatory action research approach with planning-acting-observing-reflecting cycles involving 220 participants from four educational institutions (Madrasah Ibtidaiyah, Madrasah Tsanawiyah, Madrasah Aliyah, Taman Pendidikan Al-Qur'an). Data were collected through pre-post religious literacy assessments, structured participatory observation, in-depth interviews with 15 key informants, and focus group discussions. Data analysis utilized mixed methods with descriptive statistics for quantitative data and thematic analysis for qualitative data. Results demonstrated significant improvement in religious literacy scores from baseline 52.3 to 78.7 (p<0.05), a 67% increase in active participation in religious activities, and the formation of 8 local da'wah cadres ensuring program sustainability. The Service Learning model effectively integrates academic learning with community empowerment through culturally responsive approaches that optimize local assets and create community-based sustainability mechanisms.